2019
DOI: 10.1126/science.aaw2719
|View full text |Cite
|
Sign up to set email alerts
|

Microbial metabolites control the thymic development of mucosal-associated invariant T cells

Abstract: How the microbiota modulate immune functions remains poorly understood. Mucosal-associated invariant T (MAIT) cells are implicated in mucosal homeostasis and absent in germ-free mice. Here, we show that commensal bacteria govern murine MAIT intrathymic development, as MAIT cells did not recirculate to the thymus. MAIT development required RibD expression in bacteria, indicating that production of the MAIT antigen 5-(2-oxopropylideneamino)-6-d-ribitylaminouracil (5-OP-RU) was necessary. 5-OP-RU rapidly traveled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
216
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(246 citation statements)
references
References 33 publications
9
216
0
Order By: Relevance
“…17 Finally, in a process affecting all mucosal surfaces, it was shown that bacterial metabolites of vitamin B2 are required before weaning to induce the generation of mucosa-associated invariant T (MAIT) cells in the adult. 44,45 The weaning reaction Another twist in the story was added by the characterization of the weaning reaction. We reported that the weaning reaction is the first vigorous immune response to the colonizing intestinal microbiota after birth.…”
Section: A Fetal Time Window?mentioning
confidence: 99%
“…17 Finally, in a process affecting all mucosal surfaces, it was shown that bacterial metabolites of vitamin B2 are required before weaning to induce the generation of mucosa-associated invariant T (MAIT) cells in the adult. 44,45 The weaning reaction Another twist in the story was added by the characterization of the weaning reaction. We reported that the weaning reaction is the first vigorous immune response to the colonizing intestinal microbiota after birth.…”
Section: A Fetal Time Window?mentioning
confidence: 99%
“…iNKT cells acquire an innate-like effector memory program during thymic development and egress from the thymus expressing the transcription factor promyelocytic leukemia zinc finger (PLZF), which regulates an innate-like phenotype in iNKT and MAIT cells, as well as innate lymphoid and natural killer cells (51)(52)(53). MAIT cells egress from the thymus with a naive surface phenotype and acquire an innate-like effector memory program, including PLZF expression, during expansion in the periphery following microbial colonization (52,54). The development of mycolipid-specific T cells is largely unknown.…”
Section: Mycolipid-specific T Cell Developmentmentioning
confidence: 99%
“…Indeed, we recently showed that MAIT cells can respond to a variety of microbiome-related bacteria (Tastan et al, 2018) and that they potentially function to tune or sense the microbial ecosystem throughout mucosal tissues. Two recent papers also show that MAIT cell development and expansion is also directly dependent on the microbiome (Constantinides et al, 2019;Legoux et al, 2019;Oh and Unutmaz, 2019). In one paper, the authors show that CD4-CD8- (double negative, or DN) MAIT cells are a functionally distinct subset that migrate to the skin in mice and are potentially involved in tissue repair (Dias et al, 2018;Constantinides et al, 2019;Oh and Unutmaz, 2019).…”
Section: Discussionmentioning
confidence: 95%